2017
DOI: 10.4103/ortho.ijortho_228_17
|View full text |Cite
|
Sign up to set email alerts
|

Practice Guidelines for the Management of Multiligamentous Injuries of the Knee

Abstract: Background:Multiligamentous injuries of knee remain a gray area as far as guidelines for management are concerned due to absence of large-scale, prospective controlled trials. This article reviews the recent evidence-based literature and trends in treatment of multiligamentous injuries and establishes the needful protocol, keeping in view the current concepts.Materials and Methods:Two reviewers individually assessed the available data indexed on PubMed and Medline and compiled data on incidence, surgical versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
0
10
0
5
Order By: Relevance
“…These results were optimistic compared to those of the literature could be related to short duration of follow-up. Ankit G and al [9] , Charles L et al [8] noted in their metaanalyzes a superiority of surgical treatment compared to nonsurgical treatment for follow-up of more than 5 years. They report, however, the lack of difference between the two treatments when considering the loss of pain, knee stability and the resumption of the level of previous activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were optimistic compared to those of the literature could be related to short duration of follow-up. Ankit G and al [9] , Charles L et al [8] noted in their metaanalyzes a superiority of surgical treatment compared to nonsurgical treatment for follow-up of more than 5 years. They report, however, the lack of difference between the two treatments when considering the loss of pain, knee stability and the resumption of the level of previous activities.…”
Section: Discussionmentioning
confidence: 99%
“…These controversies concerns the choice between nonsurgical or surgical treatment, ligament repair or reconstruction, the use of an autologous graft or an allograft and the operating time. For this purpose several publications have been made to propose decision trees to surgeons [8,9] . Although surgical treatment has taken place over orthopedic treatment, conditions are sometimes unavailable for this surgery [2] , especially in developing countries where the technical platform is precarious and the operating equipment inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus is lacking on the use of staged or single-stage procedures, repair or reconstruction of ligaments, type of reconstruction for each ligament, the timing of surgery, graft options, the sequence of reconstruction, and postoperative rehabilitation [9]. Different treatment options have been proposed in different studies [2,7,10,[12][13][14]. These studies focus on the acute treatment of knee dislocation and multiligament injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Based on clinical research, Loh et al showed that there was a good knee stability following anterior cruciate ligament reconstruction on PCL injury patients 12 . However, the presence of graft in the tunnel fixed invalid distance results in graft tunnel horizontal and vertical relative motion in a "wiper effect" (windshield wiper effect) and a "bungee effect" 13 . Despite that, the angle between the tunnel and the graft is less than 90º, which further leads to thinning of the grafts at the tunnel portal, decrease in tension, and the gradul relaxation ("killer turn" effect) 14,15 .…”
Section: Introductionmentioning
confidence: 99%